Outcome of office hysteroscopy in postmenopausal women with red flag signs: a single centre-based study from Northern Ireland - Aggarwal, Shikha; Rahim, Maryam; Maji, Debkalyan; Debnath, Parikshit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Assessment of postmenopausal women with red flag signs like postmenopausal bleeding/ endometrial thickness ≥5 mm is needed for early detection of any pathology. Early-stage endometrial cancer detection through office hysteroscopy is one of crucial modality for effective management. Objective was to assess the outcome of office hysteroscopy in postmenopausal women with red flag sign and correlated with histopathology findings. Methods: A prospective observational study at a single facility in Northern Ireland involving 122 post-menopausal women aged ≥45 years subjected to AUB/increased endometrial thickness. Advance diagnostic examination by office hysteroscopy followed by histopathology to detect and rule out endometrial cancer and related ailments. Results: The mean age of the study population was 63.07±10.317 SD years and 91.8% were over-weight. 71.3% women had endometrial thickness <5 mm. Hysteroscopic reported for 8.2% (10 cases) endometrial cancers having diagnostic accuracy of 98.36%. The histological and hysteroscopic diagnoses were having significantly similar outcomes. Office hysteroscopy has 100% specificity and positive predictive value in detecting normal endometrium whereas 98.25% specificity and 100% negative predictive value in case for cancer detection. Conclusions: In Irish women, office hysteroscopy proved helpful in determining the pathologies that cause postmenopausal bleeding. Correlating hysteroscopic and histological findings with red flag indications should be the focus of future explorations.